ANALYSIS OF RISK FACTORS FOR CERVICAL CANCER OCCURRENCE: A CASE-CONTROL STUDY AT BANGKA BELITUNG - Dwiyanti Wulandari; Diah Eka Nugraheni; Dwie Yunita Baska; Elvi Destariyani; Suci Sholihat (Nursing Sciences Journal, 2026)
Cervical cancer ranks as the second most common malignancy among women in Indonesia, following breast cancer, and is the second leading cause of cancer-related mortality. Over 70% of cervical cancer cases are diagnosed at an advanced stage, often due to delayed detection and treatment, which significantly affects therapeutic outcomes and increases mortality rates. This study employed an observational analytic approach with a case-control design to examine the association between age at first marriage, parity, smoking habits, hormonal contraceptive use, and family history with cervical cancer incidence. A total of 116 respondents were selected and evenly divided into case and control groups (1:1 ratio). Data were collected from medical records at Dr. (H.C) Ir. Soekarno Regional General Hospital, Bangka Belitung Islands Province, in 2024. The data analysis was conducted using chi-square statistical test and multivariate logistic regression. The findings revealed that age at marriage, parity, and hormonal contraceptive use were significantly associated with cervical cancer incidence (p < 0.05). Conversely, no significant associations were observed for smoking and family history (p > 0.05). Hormonal contraceptive use and parity emerged as key determinants. These results underscore the need to reinforce cervical cancer prevention programs through targeted education on the long-term risks of hormonal contraceptive use and by enhancing routine screening coverage at the primary healthcare level.